Peran Nabi Ibrahim Dalam Keluarga Perspektif Al-Qur’an (Solusi Terhadap Fenomena Fatherless) - Khairi, Akmal (EL-EMIR Institute, 2024)
This study aims to examine the role of Prophet Ibrahim in forming a family from the perspective of the Qur'an and its relevance as a solution to the phenomenon of fatherlessness or the absence of a father figure in the family. The phenomenon of fatherlessness is currently a social problem that has a negative impact on the mental, emotional, and spiritual development of children. In this context, the role of an ideal father as exemplified by Prophet Ibrahim, becomes important to study further. The research method used is a qualitative approach with an analysis of the interpretation of the Qur'an regarding verses that describe the interaction of Prophet Ibrahim with his family, especially in terms of education, affection, and family leadership. Data were collected through a literature review, especially the book of interpretation and literature related to the phenomenon of fatherlessness. The results of the study show that Prophet Ibrahim played a central role as a father figure who not only guided his family spiritually, but also set an example in terms of sacrifice, affection, and responsibility. This example is very relevant as a solution in dealing with the phenomenon of fatherlessness in the modern era. This study concludes that the values ​​contained in the story of Prophet Ibrahim can be used as a guide in strengthening the role of fathers in the family, especially in facing contemporary social challenges.